Groundwater amphipods (Crustacea, Malacostraca) of India, with description of three new cavernicolous species - Sidorov, Dmitry; Reddy, Yenumula Ranga; Shaik, Shabuddin (Zootaxa, 2018)
Stygofaunistic surveys of peninsular India yielded, among others, three new cavernicolous amphipod taxa: Orientogidiella reducta gen. n., sp. n. in the Borra caves of Andhra Pradesh state, Bogidiella hindustanica sp. n. (Bogidiellidae) and Indoniphargus subterraneus sp. n. (Austroniphargidae) in the Kapiladevi caves of Telangana state. The new genus, Orientogidiella gen. n., is proposed to accommodate all the hitherto known species of the Bogidiella indica-group. This paper gives an illustrated description of the three new species together with their taxonomic affinities. A new record of O. indica comb. n., from the Guthikonda caves in Andhra Pradesh is provided as well. The structure of the Indoniphargus mandible is revisited with scanning electron microscopy (SEM) and revealed a poorly known flexible structure on the molar process which could be useful for phylogenetic purposes. The species diversity and geographic distribution of the Indian stygobiotic amphipods are briefly reviewed.